Sistema de conciliación fiscal en comic - Champutiz Martínez, Iván Genaro; Figueroa Cuarán, Lilia Maureny; Torres Torres, Claudia Maritza (Boletín Informativo CEI, 2021)
Sistema de conciliación fiscal en comic